Non-invasive Brain Stimulation for the Treatment of Gilles de la Tourette Syndrome - Kleimaker, Maximilian; Kleimaker, Alexander; Weissbach, Anne; Colzato, Lorenza S.; Beste, Christian; Bäumer, Tobias; Münchau, Alexander (Frontiers in Neurology, 2020)
Gilles de la Tourette Syndrome is a multifaceted neuropsychiatric disorder typically commencing in childhood and characterized by motor and phonic tics. Its pathophysiology is still incompletely understood. However, there is convincing evidence that structural and functional abnormalities in the basal ganglia, in cortico-striato-thalamo-cortical circuits, and some cortical areas including medial frontal regions and the prefrontal cortex as well as hyperactivity of the dopaminergic system are key findings. Conventional therapeutic approaches in addition to counselling comprise behavioral treatment, particularly habit reversal therapy, oral pharmacotherapy (antipsychotic medication, alpha-2-agonists) and botulinum toxin injections. In treatment-refractory Tourette syndrome, deep brain stimulation, particularly of the internal segment of the globus pallidus, is an option for a small minority of patients. Based on pathophysiological considerations, non-invasive brain stimulation might be a suitable alternative. Repetitive transcranial magnetic stimulation appears particularly attractive. It can lead to longer-lasting alterations of excitability and connectivity in cortical networks and inter-connected regions including the basal ganglia through the induction of neural plasticity. Stimulation of the primary motor and premotor cortex has so far not been shown to be clinically effective. Some studies, though, suggest that the supplementary motor area or the temporo-parietal junction might be more appropriate targets. In this manuscript, we will review the evidence for the usefulness of repetitive transcranial magnetic stimulation and transcranial electric stimulation as treatment options in Tourette syndrome. Based on pathophysiological considerations we will discuss the rational for other approaches of non-invasive brain stimulation including state informed repetitive transcranial magnetic stimulation.